Back Cover: Enhancing the Value of Free Metals in the Synthesis of Lanthanoid Formamidinates: Is a Co‐oxidant Needed? (Chem. Eur. J. 1/2016). Issue 1 (3rd December 2015) - Deacon, Glen B.; Junk, Peter C.; Werner, Daniel
Abstract : Treatment of N, N ′‐bis(aryl)formamidines, with either europium or activated ytterbium metal in CH3 CN, is an efficient synthesis of divalent formamidinate complexes without need of a co‐oxidant, thereby completely circumventing the use of either salt metathesis, or redox transmetallation/protolysis (RTP) protocols. The background shows an outline of the state of Victoria (Australia) home to some of the authors. In particular Melbourne will be hosting the XXVII International Conference on Organometallic Chemistry (XXVII ICOMC) 17–22 July, 2016. All fields of Organometallic Chemistry will be considered, from fundamental to applied areas, including multidisciplinary approaches and related areas of other sciences. We welcome you to attend. More information on this study can be found in the Full Paper by G. B. Deacon, P. C. Junk, and D. Werner onpage 160 ff.